(untitled) (Journal of Medical & Health Sciences Review, 2025)
Ectopic pregnancy (EP) remains a leading cause of first-trimester maternal mortality worldwide. This study was conducted at DHQ Hospital Faisalabad to assess diagnostic and management strategies with a focus on ultrasonography. Thirty patients aged 22–37 years diagnosed with EP were evaluated between April and May 2024. Data included demographics, risk factors, gestational age, site of EP, and presenting symptoms. Transvaginal ultrasound combined with β-hCG was the main diagnostic tool. Results revealed that fallopian tube was the most common site, while smoking, previous cesarean section, and prior tubal surgery were notable risk factors. Abdominal pain and vaginal bleeding were the most frequent symptoms. Ultrasonography proved to be highly sensitive and non-invasive, making it the gold standard for EP diagnosis. Early detection is vital to minimize morbidity, mortality, and preserve fertility. Ectopic pregnancy, affecting about 2% of pregnancies, is a serious condition where the fertilized egg implants outside the uterus, most often in the fallopian tube. It poses significant risks to maternal health and can be fatal if untreated. Diagnosis relies mainly on transvaginal ultrasound and serial β-hCG testing.